1-D/2-D/3-D Hopfield Associative Memories. Issue 1 (January 2021) - Garimella, Rama Murthy; Singh, Aman; Jyothi Prasanna, GC; Jagannadan, Manasa; Vankam, Vidya Sree; Bairaju, Maha Lakshmi
Abstract: In this research paper storage as well as retrieval of 1-D/2-D/3-D information using Hopfield type Associative Memories (AMs) is discussed. Various Artificial Neural Networks(ANN) architectures are proposed. Also, implementational issues associated with those Associative Memories are discussed. Cascade connection of AM and Convolutional Neural Network is proposed for noise immunity.